Komunikasi Politik Mohammad Natsir - Roni Tobroni (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2017)
This study aims to reveal aspects of political communication made by M. Natsir when formulating, socialize, until the date of the adoption by MPRS integral motion. This study uses qualitative descriptive approach, so as to reveal the fact that more comprehensive. This study has revealed a struggle that is not simply how a motion integral before being accepted and confirmed by parliament. M. Natsir when trusted to formulate make the concept of unification of Indonesia in response to the threat of disintegration, he conducted political lobbies are quite long, before finally when dipidatokan no interruptions and obstacles of other MPs. These findings make clear that aspects of political communication becomes very important in reading a historical fact related to the socialization integral motion Natsir.